Do Supplementary Jobs for Welfare Recipients Increase the Chance of Welfare Exit? Evidence from Germany - Alexander Mosthaf; Thorsten Schank; Stefan Schwarz (Institute of Labor Economics (IZA), 2021)
Welfare recipients in Germany are allowed to take up supplementary jobs while receiving welfare. The possibility of having a supplementary job was introduced to reduce welfare dependency and facilitate successful labor market integration. In the present study, we use the German Panel Study "Labour Market and Social Security" (PASS) for the years 2006-2014 to analyze the impact of supplementary jobs on the chances of welfare exit. Dynamic multinomial logit models controlling for unobserved heterogeneity and the problem of initial conditions reveal that (part- and full-time) employed males are more likely to exit welfare receipt into employment than their non-employed counterparts. This effect is not driven by household composition changes or earnings increases of household members. For women, however, we find only stepping stone effects for full-time supplementary jobs during welfare receipt. Women having a supplementary part-time job have an even lower probability of leaving welfare into full-time employment.
Keywords: C33; J60; I38; 330; supplementary jobs; labor market mobility; state dependence; stepping stone effect; dynamic panel data models